Pronounced increase in risk of acute ST-segment elevation myocardial infarction in younger smokers. Issue 8 (29th November 2016) - Lloyd, Amelia; Steele, Lloyd; Fotheringham, James; Iqbal, Javaid; Sultan, Ayyaz; Teare, M Dawn; Grech, Ever D
Abstract : Objectives: Previous studies have shown that smokers presented with ST-segment elevation myocardial infarction (STEMI) a decade earlier than non-smokers. However, no account has been made for population smoking trends, an important deficit addressed by this study. Methods: The combination of admission data on patients with acute STEMI undergoing percutaneous coronary intervention and demographic data supplied by the Office for National Statistics for the South Yorkshire population between 2009–2012 were analysed to generate incidence rates and rate ratios (RR) to quantify the relative risk of STEMI from smoking, overall and by age group. Results: There were 1795 STEMI patients included of which 72.9% were male. 68 patients were excluded as they had no smoking status recorded, leaving 48.5% of the remaining population as current smokers, 27.2% ex-smokers and 24.3% never smokers. Smokers were over-represented with overall smoking prevalence in South Yorkshire calculated at 22.4%. The incidence of STEMI in smokers aged under 50, 50–65 and over 65 years was 59.7, 316.9 and 331.0 per 100 000 patient years at risk compared to 7.0, 60.9 and 106.8 for the combined group of ex- and never smokers. This gave smokers under the age of 50 years an 8.47 (95% CI 6.80 to 10.54) increase in rate compared to non-smokers of the same age, with the 50–65 and over 65 age groups having RRs of 5.20 (95% CI 4.76 to 5.69) and 3.10 (95% CI 2.67 to 3.60), respectively. Conclusions: Smoking was associated with an eightfold increased risk of acute STEMI in younger smokers, when compared to ex- and never smokers. Further efforts to reduce smoking in the youngest are needed.